The concept of student ethnocultural competence - Baowen, Lu (Educological discourse, 2022)
The article presents the results of the study on the definition of the concept of "ethno-cultural competence". To define and analyze this complex definition, derivative definitions of "ethnoculture", "culture", "competence", "ethnocultural competence" in the philosophical, pedagogical, psychological aspects have been analyzed. Analyzing and summarizing the above concepts, it is noted that ethnocultural competence manifests itself in a certain manner of behaviour in relation to the native culture or culture in the habitats of any ethnic group, helps individuals to be adequate, adapted and harmonious both for themselves and for representatives of a particular society. The results of the study showed that the concept of "ethno-cultural competence" and its derivative concepts have different definitions and are focused on determining the place of a person in the system of social coordinates and are aimed at accepting the main pattern of interethnic interaction in various aspects of human interaction. The main components accumulating the determination of ethnocultural competence of students include: adaptability to intercultural interaction, tolerance, awareness of the peculiarities of ethnocultural relations in a particular territory or social group, openness to new cultural features, etc. Based on the analysis of the research by scientists in the field of ethno-cultural interaction, our own definition of this concept has been formulated. Ethnocultural competence is defined as a multi-level construct of knowledge, skills and abilities in the field of ethnic and cultural diversity, aimed at developing intercultural understanding and acceptance of this ethnocultural diversity in oneself and others.